New archaeozoological results from Asa Koma (Djibouti): Contributing to the understanding of faunal exploitation during the 3rd millennium BC in the Horn of Africa - (:unkn) unknown (My University, 2018)
Asa Koma is a site in Djibouti, located about 30 km from the modern-day shoreline of Lake Abbe. One group of radiocarbon dates places the occupation in the middle of the 3rd millennium BC while a second pushes the occupation to the beginning of the 2nd millennium BC. We discuss this point in this paper. It is a key site for understanding the first food-production societies in the Horn of Africa because it is one of the earliest sites in the region that has yielded domestic cattle remains. Nevertheless, domesticates seem to have played only a secondary role in Asa Koma's economy. Fish represent by far the most important food resource, and fishing was most likely the main reason why people chose to live at Asa Koma. The site has been the subject of many studies. This paper presents new data that complement these previous studies, namely, a geomorphological assessment of the site and the region, results from a new testexcavation, and results from the study of an additional sample of fish remains. We estimate the mass provided by the different taxa in order to evaluate what proportion of the diet derived from fishing, hunting and stock breeding, respectively. We also summarize and reconsider the hypothesis formulated in a previous study about the season of catch and the processing of the catch for storage. We argue that Lake Abbe was very close to the site at the time of the occupation, and we suspect that fishing (and hence occupation of the site) took place during the annual floods of this lake. We discuss possible indicationsfor fish storage strategies, while acknowledging that the practice of storage continues to be difficult to elucidate from the archaeological evidence.
Keywords: African Research